Unconventional secretion mediates the trans-cellular spreading of tau - Katsinelos, Taxiarchis; Zeitler, Marcel; Dimou, Eleni; Karakatsani, Andromachi; Müller, Hans-Michael; Nachman, Eliana; Steringer, Julia P.; Ruiz de Almodóvar, Carmen; Nickel, Walter; Jahn, Thomas R. (Cell reports, 2018)
The progressive deposition of misfolded hyperphosphorylated tau is a pathological hallmark of tauopathies, including Alzheimer’s disease. However, the underlying molecular mechanisms governing the intercellular spreading of tau species remain elusive. Here, we show that full-length soluble tau is unconventionally secreted by direct translocation across the plasma membrane. Increased secretion is favored by tau hyperphosphorylation, which provokes microtubule detachment and increases the availability of free protein inside cells. Using a series of binding assays, we show that free tau interacts with components enriched at the inner leaflet of the plasma membrane, finally leading to its translocation across the plasma membrane mediated by sulfated proteoglycans. We provide further evidence that secreted soluble tau species spread trans-cellularly and are sufficient for the induction of intracellular tau aggregation in adjacent cells. Our study demonstrates the mechanistic details of tau secretion and provides insights into the initiation and progression of tau pathology.
Gesehen am 10.12.2019